Role of the 4G/5G Polymorphism of PAI-1 Gene Promoter on PAI-1 Levels in Obese Patients - Sartori, Maria Teresa; Vettor, Roberto; De Pergola, Giovanni; De Mitrio, Vito; Saggiorato, Graziella; Mea, Paolo Della; Patrassi, Giovanni Maurizio; Lombardi, Anna Maria; Fabris, Roberto; Girolami, Antonio (Thrombosis and Haemostasis, 2001)
As PAI-1, a cardiovascular risk factor linked to insulin-resistance, may be influenced by a 4G/5G gene polymorphism in disease states, we studied both PAI-1 plasma concentration (PAI-1:Ag) and 4G/5G polymorphism, and their relationship with anthropometric and endocrine-metabolic parameters in 93 obese patients and 79 lean normal subjects. In obese patients PAI-1:Ag levels were significantly increased, namely in males and in those with central obesity, and tightly related to the insulin-resistance parameters.In obese patients the 4G/5G polymorphism was a determinant of PAI-1:Ag levels, which were highest in 4G/4G, intermediate in 4G/5G and lowest in 5G/5G genotype carriers. PAI-1:Ag levels were significantly associated with most of anthropometric and endocrine-metabolic parameters only in 4G allele obese carriers. Moreover, only in patients with central obesity was the relationship between genotype and PAI-1 concentration maintained, with the highest levels in the 4G/4G patients. In each genotype subset of patients with central, but not peripheral, obesity PAI-1:Ag levels were significantly increased compared to their lean counterparts.In conclusion, the 4G/5G polymorphism may influence PAI-1 expression in obesity, with a crucial role in central but not peripheral adiposity. Since subjects with central obesity are at high risk for cardiovascular disease, the effects of the 4G/5G polymorphism on PAI-1 concentration may further enhance this risk.
Keywords: PAI-1; PAI-1 gene polymorphism; obesity; insulin-resistance; risk markers